TAKSONOMI BERPIKIR SPASIAL (TAXONOMY OF SPATIAL THINKING) DAN KESESUAIANNYA DI SMAN 1 TOMOHON - Syafrida Selfiardy (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
One measure of the impact of a new idea in geography education is how well the idea is put into everyday practice. Spatial thinking skills are actually not a new idea in geography education; Spatial analysis has long been one of its core traditions but the use of the term is new and has only just begun to be widely used. Spatial thinking skills are the use of spatial concepts such as distance, direction, and area; representational tools such as maps and graphs; along with appropriate thought processes, to conceptualize and solve problems. The aim of this article is to help teachers incorporate spatial thinking into their instruction through a concrete tool, the taxonomy of spatial thinking, applied to tried and true strategies of pedagogical questioning, both in text and in a classroom context. Our main premise is that students' spatial thinking can, and should, be facilitated by the careful design, selection, and use of questions.